THE PSYCHOLOGICAL IMPACT OF COVID-19 PANDEMIC IN CAREGIVERS OF CORONAPOSITIVE PATIENTS ADMITTED IN GURU NANAK DEV HOSPITAL UNDER GOVERNMENT MEDICAL COLLEGE, AMRITSAR - ARORA, RAJIV; SINGH, KHUSHBINDER; KAUR, MANMEET; SIDHU, RAMINDER (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to find out the sociodemographic profile and psychological impact of COVID-19 pandemic in the key caregivers of COVID-19 patients. Methods: The psychological impact of COVID-19 pandemic was measured using DASS-21 scale in a sample of 100 caregivers of corona-positive patients admitted in Guru Nanak Dev Hospital under Govt. Medical College. Results: In our study, majority of the family caregivers of corona-positive patients in the hospital setting were male (76%), belonged to 21–40 years age group (58%), wedded (64%), Sikh by religion (69%), employed (58%), and from rural region (56%). Caregivers showed extremely severe depression (30.58±6.521), extremely severe anxiety (29.34±7.130), and severe stress (29.14±5694). Participants with increasing age showed higher levels depression, anxiety, and stress scores but significant association was seen only with mean anxiety scores with increasing age (p<0.05). A significant association was seen between mean scores of stress and education status (p<0.05). A significant association was also seen between mean scores of anxiety and stress scores and nuptial status (p<0.05). No significant associations were seen between gender of caregivers, employment status, religion, family type, and mean depression, anxiety, and stress scores (p>0.05). Conclusion: The impact of COVID-19 pandemic on mental health of family caregivers of COVID-19 cases is significant.